Development of augmented reality-based flashcard learning media for teaching leaf types - Siregar, Dwi Aninditya; Siregar, Nabilah; Nasution, Sari Rozi Wahyuni; Nasution, Hanifah Nur (JPBIO (Jurnal Pendidikan Biologi), 2025)
The use of this medium is expected to help students better understand and retain information about leaves, thereby contributing to improved learning outcomes in biology as a whole. This study aims to develop an effective Augmented Reality (AR)-based flashcard learning medium for the topic of leaf types. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 25 biology education students who had completed the Plant Morphology course, selected through a purposive sampling technique. The validation results indicated that the AR flashcard learning medium demonstrated a very high level of feasibility. Media expert validation obtained a score of 89.3%, while material expert validation yielded a score of 90%, both categorized as “highly feasible.” Furthermore, the evaluation based on educators’ responses achieved a score of 100%, also classified as “highly feasible.” These findings suggest that the AR-based flashcard learning medium received highly positive responses and proved effective in enhancing students’ interest and motivation in learning plant morphology.